PENGARUH INSENTIF DAN KECERDASAN INTELEKTUAL TERHADAP EFISIENSI KERJA KARYAWAN PT INDO GLOBAL SUMATERA MEDAN - Fransciskus Fransciskus; Imanuel Tarigan; Syawaluddin Syawaluddin (STIE-PMCI, 2021)
This research was conducted at PT Indo Global Sumatera Medan. The purpose of this study was to investigate and analyze the Effect of Incentives and Intellectual Intelligence on the Work Efficiency of Employees at PT Indo Global Sumatera Medan. The population numbered 35 employees while the sample in this study were: 35 employees. The sampling technique used is saturation sampling. Data collection techniques are the distribution of questionnaires, interviews and documentation studies and literature studies. Data analysis uses multiple linear regression analysis. The conclusion of the study is that simultaneous incentives and intellectual intelligence have a positive and significant effect on the work efficiency of the employees of PT Indo Global Sumatera Medan. Partially the incentives have a positive and significant effect on the Employee Efficiency of PT Indo Global Sumatera Medan. Partially Â Intellectual Intelligence has a positive and significant effect on the Work Efficiency of Employees at PT Indo Global Sumatera Medan. Adjusted R Square is: equal to 0.473 means that the Incentives and Intellectual Intelligence can explain the Work Efficiency of Employees of PT Indo Global Sumatera Medan by 47.3% and the remaining 52.7% (100-47.3) is influenced by other variables outside of this study such as : salary, promotion and so onKeywords: Incentives, Intellectual Intelligence, Employee Work Efficiency.